Exploration of the Role of Music Therapy in Reducing Dental Anxiety - Abdalwhab Zwiri; Mohammad Khursheed Alam; Wroud Alturqi Alshammari; Fatimah Mazyad Almazyad; Nor Farid Bin Mohd Noor (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: A large percentage of patients suffer from dental anxiety, which often results in poor oral health and avoidance of dental treatment. One noninvasive, reasonably priced strategy that may help with anxiety management is music therapy. Materials and Methods: For this randomized controlled experiment, 60 individuals with self-reported dental anxiety, aged 18–50 years, were included. Participants were split into two groups: Group B (n = 30) had dental treatments without music therapy, and Group A (n = 30) had music therapy during those procedures. The Modified Dental Anxiety Scale (MDAS) was used to measure dental anxiety both before and after the surgery. Blood pressure and heart rate were also assessed as physiological markers of anxiousness. Results: Following music therapy, the mean MDAS score in Group A dropped significantly (P < 0.01) from 18.5 ± 2.3 to 12.7 ± 2.1. Additionally, physiological measures, including blood pressure and heart rate, showed a substantial decrease (P < 0.05). However, Group B showed no significant changes in physiological indicators and a little decrease in MDAS scores (from 17.9 ± 2.4 to 16.8 ± 2.5, P > 0.05). Conclusion: Significant changes in psychological and physiological indicators demonstrate that music therapy is a beneficial strategy for lowering dental anxiety. Patients’ comfort and overall treatment experiences may be improved by integrating music therapy into dental practices.